2016
DOI: 10.1186/s12903-016-0289-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of early childhood caries among children in Beijing: a case-control study

Abstract: BackgroundThe prevalence of early childhood caries (ECC) among children in Beijing, China, has been increasing continuously though slowly. However, there is limited information about ECC in Beijing. The aim of this study was to identify risk factors of dental caries among preschool children in Beijing.MethodsFor this case-control study, using a convenience sampling method, 787 children aged 3 and 4 years old were recruited; 386 children with caries constituted the early childhood caries (ECC) group and 401chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 24 publications
3
31
0
4
Order By: Relevance
“…This study showed that the prevalence of dental caries among 3-year olds children in Wenzhou was 59.8%; it was higher than the prevalence of ECC in 3-4 years old in Beijing (49%) [ 8]. On average, the prevalence of dental caries among 3 years old children in China was 50.8% [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that the prevalence of dental caries among 3-year olds children in Wenzhou was 59.8%; it was higher than the prevalence of ECC in 3-4 years old in Beijing (49%) [ 8]. On average, the prevalence of dental caries among 3 years old children in China was 50.8% [6].…”
Section: Discussionmentioning
confidence: 99%
“…Declines in the prevalence of dental caries were observed in the developed countries during last three decades [ 4]. In contrast, because of the easy availability of refined sugars than earlier, compromised dental care and prevention, very few programs to eradicate the disease and poor public knowledge about the disease, dental caries in China has become a new threat and been on the rise [ 5,6,7,8]. The Third National Oral Health Epidemiology Survey reported that the prevalence of caries was 66% and the mean decayed, missing, and filled primary teeth (dmft) score was 3.5 among 5-year-old children in China [ 7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, visible dental plaque is an important predictor of new carious lesions. 9,24,25 Another factor significantly associated with ECC was the type of health insurance coverage. The group categorized as FONASA A had a higher mean dmft index.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when a child takes a bottle containing milk to bed, milk pools around the teeth and, as there is less saliva flow at night, the milk remains in the mouth, and the lactose is broken down to produce lactic acid. Other behaviours such as parents sampling foods before feeding their child and children sharing utensils also enable transmission of cariogenic bacteria to young children (Fan, Wang, Xu, & Zheng, 2016; Sakai et al, 2008).…”
Section: Introductionmentioning
confidence: 99%